Wind River Sap Flux - Patrick Sullivan (Arctic Data Center, 2016)
Hourly sap flux data for the growing seasons of 2013-2016 in a low density white spruce stand on the Wind River in the Arctic National Wildlife Refuge, eastern Brooks Range.